Analysis of Revitalization Practices for Division of Heritage and Implications in Muslim Society - Fakhrun Khair (Universitas Serang Raya, 2024)
This can raise a variety of practical problems, especially in terms of the fulfillment of the daily needs of heirs who may be controlled by the long-standing process of inheritance division that the Investigator will investigate the practice of rejuvenation of the division of the Muslim community, and how the implications of this research use normative law research, with the pointing of the law as the building of the norm system, thus the data used is secondary data referring to a set of data, including qualitatively analyzed library studies and documentation, the use of the will to regulate the partition of the heritage into an emerging trend, the implementation of accelerated partition practices in Muslim communities has a significant positive impact, the distribution of the legacy fairly and quickly, minimizing potential conflicts and conflicts in the family, strengthening social bonds and family bonds in the entire Muslim community barbarslot. There are still obstacles and challenges to be overcome in implementing these practices widely and collaborative efforts are needed to address these issues so that accelerating the division of heritage can become a sustainable norm within the Muslim community.